School Based Management of School Administrators of Sai Mai District Office, Bangkok Metropolitan - ภูธนัญภิรมย์, จิณณ์ประกฤษฎิ์; ชวศิริกุลฑล, นันทนา; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were to: 1) investigate the school-based management practices of school administrators; 2) compare school-based management practices classified by educational level, work experience, and school size; and 3) propose guidelines for developing school-based management among school administrators under the Sai Mai District Office, Bangkok Metropolitan Administration. The sample consisted of 241 teachers from schools under the Sai Mai District Office, Bangkok Metropolitan Administration. The sample size was determined using the Krejcie and Morgan (1970) formula, and selected through stratified random sampling and simple random sampling. The research instruments employed in this study consisted of a questionnaire administered to teachers, focusing on school-based management of school administrators under the Sai Mai District Office, Bangkok. The questionnaire yielded a reliability coefficient of 0.97, indicating high internal consistency. Additionally, structured interviews were conducted with five key informants, comprising three Senior Professional Level teachers and two heads of learning area departments. The statistics used for data analysis included frequency, percentage, mean, and standard deviation. Hypothesis testing was conducted using an independent t-test and one-way ANOVA (F-test). When statistically significant differences were found, Scheffe’s method was used for pairwise comparison. Content analysis was applied to qualitative data using semi-structured interview.           The research results were found that 1) overall, the school-based management of educational administrators was at a high level. When considering each aspect, accountability had the highest mean, followed by whole-system development, while decentralization had the lowest mean, though still at a high level. 2) The comparison of school-based management, classified by education level and school size, showed no statistically significant differences overall. However, differences in work experience showed statistically significant differences at the .05 level. (3) The findings suggested that administrators should appropriately decentralize authority, promote school autonomy, encourage participation from all stakeholders in decision-making, demonstrate supportive leadership, support and motivate personnel, implement holistic school development, and ensure transparency and accountability. These practices contributed to effective administration and enhanced the overall quality of education.